Verifiable access control scheme based on unpaired CP-ABE in fog computing - Jiangtao DONG; Peiwen YAN; Ruizhong DU (Tongxin xuebao, 2021)
Fog computing extends computing power and data analysis applications to the edge of the network, solves the latency problem of cloud computing, and also brings new challenges to data security.Attribute encryption based on ciphertext strategy (CP-ABE) is a technology to ensure data confidentiality and fine-grained access control.The excessive computational overhead of bilinear pairing restricts its application and development.In response to this, a verifiable access control scheme was proposed based on unpaired CP-ABE in fog computing.In order to make CP-ABE more efficient, simple scalar multiplication in elliptic curve encryption was used to replace bilinear pairing, thereby reducing the overall computational overhead.Decryption operations were outsourced to fog nodes to reduce user computational complexity, and based on the tamper-proof and traceable characteristics of the blockchain, the correctness of the access transaction was verified and the access authorization process was recorded.Security and performance analysis shows that the scheme is safe under the elliptic curve decision-making DBDH (Diffie-Hellman) assumption, and the calculation efficiency is higher.